2011
DOI: 10.1111/j.1747-0803.2011.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Right Ventricular Outflow Tract Hemangioma in an Adolescent

Abstract: Cardiac tumors are rare in children, but they are being diagnosed with increasing frequency and great accuracy with wide array of imaging modalities. Cardiac rhabdomyoma and myxoma are the most common tumors in children and adults, respectively. Cardiac hemangiomas comprise about 2.8% of all primary cardiac tumors and fewer than 100 cases have been reported in the literature. We report a successful resection of cardiac hemangioma in the right ventricular outflow tract in an adolescent, presented with moderate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Highlighting the rarity of these lesions, our own review of the literature has revealed eight subsequent case reports on primary vascular tumours of the heart in children. [8][9][10][11][12][13] Laga et al, Watanabe et al, and Sharma et al [8][9][10] have described five cases of neonatal haemangioma, two of which were associated with an evolving tamponade requiring emergent intervention. Moniotte et al 11 have described the case of a 12-year-old boy presenting with a heart murmur diagnosed by echocardiography and magnetic resonance imaging with a pedunculated haemangioma associated with the right ventricular outflow tract, which was successfully resected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highlighting the rarity of these lesions, our own review of the literature has revealed eight subsequent case reports on primary vascular tumours of the heart in children. [8][9][10][11][12][13] Laga et al, Watanabe et al, and Sharma et al [8][9][10] have described five cases of neonatal haemangioma, two of which were associated with an evolving tamponade requiring emergent intervention. Moniotte et al 11 have described the case of a 12-year-old boy presenting with a heart murmur diagnosed by echocardiography and magnetic resonance imaging with a pedunculated haemangioma associated with the right ventricular outflow tract, which was successfully resected.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of death in this patient was not clearly proven but was hypothesised to be related to ventricular arrhythmia. 12 Most recently, Sharma et al 13 reported the successful resection of an obstructive haemangioma in the right ventricular outflow tract, which presented in adolescence.…”
Section: Discussionmentioning
confidence: 99%